Present and future of the critically endangered Araucaria angustifolia due to climate change and habitat loss. (5th December 2019) - Marchioro, Cesar A; Santos, Karine L; Siminski, Alexandre
Abstract: The critically endangered Brazilian pine, also called araucaria, ( Araucaria angustifolia (Bertol.) Kuntze) is a key species of the Araucaria moist forest (AMF, Mixed Ombrophilous Forest). Illegal timber extraction, agricultural conversion and severe degradation have reduced the AMF to only 13 per cent of its original cover, with climate change imposing additional challenges for cold adapted species such as araucaria. Previous studies have assessed climate change impacts on A. angustifolia, but have been limited by analysis constraints. Here, we used a machine learning technique to understand how land use and climate change might affect the distribution of A. angustifolia, and to evaluate the effectiveness of existing protected areas (PAs) to conserve this species. Our results demonstrated that despite the recent efforts to conserve the Atlantic Forest, conversion of natural habitats into forest plantation still occurs within araucaria's distribution range. Our model predicted a drastic reduction in environmentally suitable areas for this species of up to 77 per cent in the coming decades. Also, the existing PAs show low efficacy to protect suitable areas in the future. Combined, these results suggest that A. angustifolia will be under great threat within the next few decades and the development of conservation strategies to save this species is essential. Ideally, the conservation programs should integrate in situ and on farm approaches, including forest management strategies. Although in situ strategies play an important role as gene banks, on-farm strategies can be used to promote the restoration and expansion of A. angustifolia populations in the areas predicted as suitable.